Pengaruh Literasi Keuangan dan Self-Efficacy Terhadap Perilaku Keuangan - Anastasia Anggarkusuma Arofah; Rani Kurniawati (UNPERBA, 2021)
Abstract Financial behavior has an important role for individuals, because it relates to the individual's ability to achieve predetermined goals. In managing finances, a person needs more than just financial literacy but must have confidence in his abilities. This attribute is known in the psychological literature as